Stability and reliability of error‐related electromyography over the corrugator supercilii with increasing trials. (16th June 2017) - Elkins‐Brown, Nathaniel; Saunders, Blair; He, Frank; Inzlicht, Michael
Abstract: Electromyographic activity over the corrugator supercilii (cEMG), the primary facial muscle involved in negative emotions, is increased during the commission of errors on speeded reaction‐time tasks. In the present paper, data from two previously published studies were reanalyzed to investigate the reliability and stability of error‐related, correct‐related, and difference cEMG across increasing numbers of trials. For a modified go/no‐go and a flanker task, we found that error‐related cEMG was highly stable and reliable in 14 trials, and correct‐related cEMG between 56 and 82 trials, respectively. Given the typical number of trials used in studies of cognitive control, these findings suggest that many investigations of error monitoring are already sufficient to obtain acceptable error‐ and correct‐related cEMG signals. Error‐related cEMG activity is relatively easy to measure and, as such, it shows great promise for future research investigating the cognitive and affective mechanisms of error monitoring.